Strength Training for the Intrinsic Flexor Muscles of the Foot: Effects on Muscle Strength, the Foot Arch, and Dynamic Parameters Before and After the Training - Hashimoto, Takayuki (The Society of Physical Therapy Science, 2014)
[Purpose] The purpose of the present study was to verify the effects of intrinsic foot flexor strength training. [Subjects] The subjects were 12 healthy males without motor system disease. [Methods] A training method that involved flexion of all toe interphalangeal and metatarsophalangeal joints against a 3-kg load was implemented and was performed for 200 repetitions once per day, three times per week, for a period of eight weeks. [Results] Significant changes were observed for intrinsic foot flexor strength scores, foot arches, vertical jumping, 1-legged long jumping, and 50-m dash time. [Conclusion] This muscle strength training method significantly improved muscle strength scores, foot arch shape, and movement performance.